2009
DOI: 10.1016/j.ijrobp.2009.07.1310
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Method of Adaptive Radiotherapy for Prostate Cancer using Real-time Electromagnetic Tracking

Abstract: Purpose/Objectives-We have created an automated process utilizing real-time tracking data to evaluate adequacy of PTV margins in prostate cancer, allowing for a process of adaptive radiotherapy with minimal physician workload. We present an analysis of PTV adequacy and a proposed adaptive process.Materials/Methods-Tracking data was analyzed for 15 patients who underwent SMLC IMRT with uniform 5mm PTV margins for prostate cancer utilizing the Calypso® Localization System. Additional plans were generated with 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…22 One paper which accounts for rotations and translations proposed a uniform margin of 5 mm when used with a 3-mm online correction protocol and <10 degree rotation allowance. 23 This is in agreement with our findings that prostate geographical miss may not be represented by all fiducial translations (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…22 One paper which accounts for rotations and translations proposed a uniform margin of 5 mm when used with a 3-mm online correction protocol and <10 degree rotation allowance. 23 This is in agreement with our findings that prostate geographical miss may not be represented by all fiducial translations (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…[13][14][15] Other studies have measured inter-and intrafraction prostate rotations [16][17][18] and the dosimetric impact of rotations. 19 Many strategies have been investigated to manage prostate rotations through appropriate PTV margins, [20][21][22] motion management devices, 23 rotation compensations with the table, collimator or gantry, 24,25 and adaptive replanning. 21,26,27 Given the risks of catheter placement, including urinary tract infections and discomfort, we utilized data from a multiinstitutional prostate SBRT study conducted from 2011 to 2013 to better determine the impact and benefit of the Foley catheter placement.…”
Section: Introductionmentioning
confidence: 99%
“…19 Many strategies have been investigated to manage prostate rotations through appropriate PTV margins, [20][21][22] motion management devices, 23 rotation compensations with the table, collimator or gantry, 24,25 and adaptive replanning. 21,26,27 Given the risks of catheter placement, including urinary tract infections and discomfort, we utilized data from a multiinstitutional prostate SBRT study conducted from 2011 to 2013 to better determine the impact and benefit of the Foley catheter placement. The goal of the project was to investigate whether two CT simulation scans were necessary and if treatment planning could be performed on the FCT alone, or on the TPCT without a Foley at all.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work performed by Olsen et al using the SWIFTER application found considerable variation in motion-compensated dosimetry for prostate cancer patients displaying the same general characteristics and treatment schemes. 24 The authors concluded that different margins were appropriate for different patients, and that SWIFTER was important in indentifying individualized margin adequacy. A basic comparison between the plan dose parameters and estimated delivered dose parameters (Table I) indicates that the 0 mm margin treatment plan is more susceptible to motion than the 3 and 5 mm margin treatment plans.…”
Section: Discussionmentioning
confidence: 99%